2023
DOI: 10.1021/acsabm.3c00072
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Derived Primary Cell Type Dictates the Endocytic Uptake Route of Carbon Quantum Dots and In Vivo Uptake

Abstract: Carbon quantum dots (CQDs) require systemic biological delivery to advance their applications in drug delivery, biosensing, and bioimaging. We describe the endocytic pathways of green-emitting fluorescent carbon quantum dots (GCQDs) with sizes varying from 3 to 5 nm in mouse tissue-derived primary cells, tissues, and zebrafish embryos. The GCQDs demonstrated cellular internalization into mouse kidney and liver primary cells via a clathrin-mediated pathway. Using imaging, we were able to identify and reinforce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The concentration of plant extracts has an essential role in the size and shape tuning of nanomaterials. Some studies have shown that increasing the concentration of plant extract resulted in a decrease in the size of nanoparticles because the higher concentration of plant extracts promotes faster reduction and stabilization [24] . The yield of nanomaterials will also increase with increasing concentration of plant extracts.…”
Section: Factors That Affect the Synthesis Of Nanomaterialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The concentration of plant extracts has an essential role in the size and shape tuning of nanomaterials. Some studies have shown that increasing the concentration of plant extract resulted in a decrease in the size of nanoparticles because the higher concentration of plant extracts promotes faster reduction and stabilization [24] . The yield of nanomaterials will also increase with increasing concentration of plant extracts.…”
Section: Factors That Affect the Synthesis Of Nanomaterialsmentioning
confidence: 99%
“…Researchers have shown considerable interest in copper nanoparticles due to their remarkable rigidity, extraordinary strength, large surface area, elasticity, and ductility. [24,65] These unique properties make copper nanoparticles highly versatile, finding extensive applications across various science and technology sectors, including biological science, chemistry, and energyrelated fields.…”
Section: Copper (Cu) Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various bottom-up methods are used for the synthesis of nanoparticles, for example, microwave, 5 hydrothermal, 6,7 and reflux. 8 The microwave method of synthesis offers great advantages over the other methods in terms of a high reaction rate and energy efficient and localized heating of precursors in a short interval of time (within minutes), thereby precisely controlling the shape and size of the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, QDs are usually used in nanoparticle endocytosis studies. More importantly, QDs have been extensively reported to be internalized primarily through clathrin-mediated endocytosis. ,, Therefore, QDs may serve as a typical tool for investigating the regulatory mechanisms of clathrin-mediated nanoparticle endocytosis.…”
mentioning
confidence: 99%